1996
DOI: 10.1038/ki.1996.535
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional and prognostic correlates of bioimpedance indexes in hemodialysis patients

Abstract: We carried out a cross sectional and longitudinal study to assess whether bioimpedance indexes (resistance, Rz; reactance, Xc; phase angle, PA) reflect the nutritional status of hemodialysis (HD) patients, and bear a significant association with their long-term survival. The bioimpedance data of 131 patients on chronic HD treatment were compared with those of 272 healthy controls matched for age and sex. Nutritional status was assessed by anthropometric variables, serum albumin (SA), normalized protein catabol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
115
0
13

Year Published

2001
2001
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 203 publications
(139 citation statements)
references
References 21 publications
8
115
0
13
Order By: Relevance
“…The PA has been used as a marker of nutritional status in clinical practice of adults6 - 9 and children13 and, when associated with anthropometric data of weight and height in patients at nutritional risk, it is a good screening tool.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The PA has been used as a marker of nutritional status in clinical practice of adults6 - 9 and children13 and, when associated with anthropometric data of weight and height in patients at nutritional risk, it is a good screening tool.…”
Section: Discussionmentioning
confidence: 99%
“…This was a secondary analysis of the study on the prevalence of malnutrition in HCFMRP-USP carried out in 2013 9. The study was approved by Institutional Review Board of HCFMRP-USP.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…20 Furthermore, this technique allows an early detection of abnormal nutritional status in physiological conditions as well as in a variety of pathological conditions, including uremia. 21 ± 26 In particular, the alterations of PA, which is an independent predictor of death in uremic patients, 25,27,28 precede the changes of biochemical nutritional parameters. 25 The current study was designed to gain insights into the in¯uence of body size, as indicated by body mass index, upon body composition in hemodialysis patients.…”
Section: Introductionmentioning
confidence: 99%
“…21 ± 26 In particular, the alterations of PA, which is an independent predictor of death in uremic patients, 25,27,28 precede the changes of biochemical nutritional parameters. 25 The current study was designed to gain insights into the in¯uence of body size, as indicated by body mass index, upon body composition in hemodialysis patients. To this aim, we performed bioimpedance analysis and anthropometry in groups of patients with different BMI.…”
Section: Introductionmentioning
confidence: 99%